The effect of the incorporation of Mg in beta tricalcium phosphate: a brief review - de Almeida, Ycaro Breno Alves; Júnior, Diógenes de Moura; Farias, José Rosa de Souza; Sales, Victória Régia Alves; Costa, Slanna Larissa Olimpio; Carvalho, Geysivana Késsya Garcia; Sobrinho, Naiara de Oliveira; dos Santos, Valdeci Bosco; Simões, Veruska do Nascimento; Braga, Aluska do Nascimento Simões (Seven Editora, 2023)
Beta tricalcium phosphate (β-TCP) is a well-known biomaterial in the area of bone substitutes, as it presents excellent biodegradability, as well as excellent biocompatible properties. Promoting greater stability and mechanical resistance to this phase, magnesium (Mg) appears as a promising candidate for doping β-TCP. Thus, this work aimed to review the effect of β-TCP doping with Mg. It has been found that small additions of Mg provide strong changes in β-TCP.DOI: https://doi.org/10.56238/devopinterscie-063